2019
DOI: 10.3390/antiox8060184
|View full text |Cite
|
Sign up to set email alerts
|

Green Alternatives to Synthetic Antioxidants, Antimicrobials, Nitrates, and Nitrites in Clean Label Spanish Chorizo

Abstract: Natural extracts obtained from fruit and vegetable processing are important sources of phenolic compounds and nitrates, with excellent antioxidant and antimicrobial properties. The aim of this study was to characterize and determine the antioxidant and antimicrobial capacity of several natural extracts (citric (Ct), acerola (Ac), rosemary (R), paprika, garlic, oregano, beet (B), lettuce (L), arugula (A), spinach (S), chard (Ch), celery (Ce), and watercress (W)), both in vitro and applied to a cured meat produc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 51 publications
(33 citation statements)
references
References 65 publications
0
32
0
1
Order By: Relevance
“…In this work, we have verified that in the quantities in which they are habitually used for culinary purposes, the very low level of essential oils (data not evaluated; this will be undertaken in future studies) does not exert the expected and reported antimicrobial effect in several research studies [ 6 , 7 , 8 , 9 , 10 , 11 , 12 , 15 , 16 , 17 , 32 , 33 , 51 , 52 , 56 , 57 , 58 , 59 ]. In these studies, the essential oils extracted from these aromatic herbs are used directly, leading to the proposal that they might be a natural alternative to inorganic chemical preservatives.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…In this work, we have verified that in the quantities in which they are habitually used for culinary purposes, the very low level of essential oils (data not evaluated; this will be undertaken in future studies) does not exert the expected and reported antimicrobial effect in several research studies [ 6 , 7 , 8 , 9 , 10 , 11 , 12 , 15 , 16 , 17 , 32 , 33 , 51 , 52 , 56 , 57 , 58 , 59 ]. In these studies, the essential oils extracted from these aromatic herbs are used directly, leading to the proposal that they might be a natural alternative to inorganic chemical preservatives.…”
Section: Discussionmentioning
confidence: 52%
“…Another extended use of these herbs, increasing the amount added to food, is the masking of undesirable flavors when they have been submitted to an inadequate state of preservation. Aromatic herbs have also been used, for their content of essential oils and polyphenolic antioxidant compounds, in traditional medicine [ 1 , 3 , 4 , 5 ], and as natural food preservatives due to the antimicrobial and antifungal action of their constituent essential oils [ 6 , 7 , 8 , 9 , 10 , 11 ]. In recent years, ethanolic extracts of rosemary at 1% in active packaging have been proposed as components of a protective film of biodegradable serum protein, as they present antimicrobial activity against L. monocytogenes [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Lipid oxidation was also related to the concentration of volatile compounds and was determined following the method described by Martínez et al [ 28 ]. Five grams of samples were placed in glass vials.…”
Section: Methodsmentioning
confidence: 99%
“…Herbs and spices are among the natural compounds that are currently being used as food preservatives, which contain compounds with marked antioxidant and antimicrobial properties [ 3 ]. Plant extracts have been used for hundreds of years to improve the organoleptic properties of food, but further to this, Chipault et al [ 4 , 5 ] reported that plant extracts also have preservative properties in different types of spices, and there is currently a lot of information about the compounds and mechanisms involved in the inhibition of lipid peroxidation [ 6 , 7 ]. They are considered to be GRAS (generally recognized as safe), which makes consumers and regulatory agencies regard them as more appropriate for use in food than artificial compounds.…”
Section: Introductionmentioning
confidence: 99%